2023
DOI: 10.21577/0100-4042.20170970
|View full text |Cite
|
Sign up to set email alerts
|

Fonte Ou Sumidouro? Uma Revisão Sobre Os Fluxos De Co2 Na Plataforma Continental Brasileira

Abstract: SOURCE OR SINK? A REVIEW OF THE CO2 FLUXES AT THE BRAZILIAN CONTINENTAL SHELF. Studies of global carbon balance estimates are still incipient in the oceans of the Southern Hemisphere, mainly in coastal areas and continental shelf. Even in Brazil, despite its continental proportion coastline, there is still a great inconsistency in studies on the marine carbonate system and CO2 fluxes at the air-sea interface. This article presents a review of studies on CO2 fluxes on the coast of Brazil, published between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(155 reference statements)
0
0
0
Order By: Relevance
“…In the following decades (2001-2010; 2011-2018), negative temporal trends were recorded, thus characterizing the area as an atmospheric CO 2 sink. Based on an extensive literature review on CO 2 fluxes along the Brazilian continental shelf, Oliveira et al 2022 found evidence of a latitudinal variation in source/ sink behavior, observing the North-Northeast as mainly CO 2 source areas, the Southeast region acting as a weak CO 2 source, and in the southern region, there is a tendency towards a permanent CO2 sink. These patterns may vary over time, depending on local oceanographic and biological processes, and different anthropogenic pressures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the following decades (2001-2010; 2011-2018), negative temporal trends were recorded, thus characterizing the area as an atmospheric CO 2 sink. Based on an extensive literature review on CO 2 fluxes along the Brazilian continental shelf, Oliveira et al 2022 found evidence of a latitudinal variation in source/ sink behavior, observing the North-Northeast as mainly CO 2 source areas, the Southeast region acting as a weak CO 2 source, and in the southern region, there is a tendency towards a permanent CO2 sink. These patterns may vary over time, depending on local oceanographic and biological processes, and different anthropogenic pressures (e.g.…”
Section: Discussionmentioning
confidence: 99%